Schwann Cells Enhance Penetration of Regenerated Axons into Three-Dimensional Microchannels - Liu, Chun (Tissue Eng Regen Med, 2018)
Nerve regeneration after injury requires proper axon alignment to bridge the lesion site and myelination to achieve functional recovery. Transplanted scaffolds with aligned channels, have been shown to induce axon growth to some extent. However, the penetration of axons into the microchannels remain a challenge, influencing the functional recovery of regenerated nerves. We previously demonstrated that the size of microchannels exerts significant impact on Schwann cells (SCs) migration. Here we demonstrate that migration of SCs promotes, significantly, the dorsal root ganglion (DRG) neurons to extend axons into three-dimensional channels and form aligned fascicular-like axon tracts. Moreover, the migrating SCs attach and wrap around the aligned axons of DRG neurons in the microchannels and initiate myelination. The SCs release growth factors that provide chemotactic signals to the regenerating axons, similar to the response achieved with nerve growth factor (NGF), but with the additional capability of promoting myelination, thereby demonstrating the beneficial effects of including SCs over NGF alone in enhancing axon penetration and myelination in three-dimensional microchannels.